ANALISA FAKTOR-FAKTOR YANG MEMPENGARUHI KEPUASAN KARYAWAN TERHADAP LINGKUP KERJANYA DAN KEPUASAN TAMU HOTEL XYZ - Siska Ayu Kartika; Bobby Oedy P Soepangkat; Sony Sunaryo (Lembaga Penelitian dan Pengabdian kepada Masyarakat- Institut Teknologi Sepuluh Nopember, 2005)
XYZ Hotel is a three stars hotel, which currently faces a problem with declining occupancy room and growth of total guest. These will become worse, if XYZ Hotel can not provide the best service as guest expectation. The ability of employee to provide service is influenced by employee’s satisfaction to their work scope which consists of character ambiguity, character conflict, competency conformity to employee’s work, technology conformity to employee’s work, control perception, control system and team work. On the other side, customer satisfaction is also influenced by service quality variables, such as tangible, reliability, responsibility, assurance and empathy.This research was done by distributing questionnaire using SERVQUAL Method (Parasuraman, et al. 1990), and only measure gap 3 and 5, using Likert scale. The result showed that factor which influenced employees satisfaction was control system. And the most important factor that influences customer satisfaction was assurance. Both of these important factor had to be a first improvement priority for management to reach customer satisfaction. Finally, based on this research, we learned that there was no significant correlation between employee and customer satisfaction in the XYZ Hotel.